Meaning Of The Phrase “Sin That Doesn't Create Death” According To 1 John 5:16 - Mitra Milawati Hia; Kasiatin Widianto (Theological Journal Kerugma, 2022)
The title of this research is as follows: The Meaning Of The Phrase “Sin That Does Not Bring Death” According To 1 John 5:16 "The purpose of this study is to prove and explain the meaning of the phrase Sin that does not bring death according to 1 John 5:16. The research method used in This study uses an exegesis study, using books as reference material for more valid literature review research requirements. There are several results as conclusions in this study, namely as follows: "sins that are not bring death" referred to in 1 John 5:16 is the sin of believers (those who have been born again) who have sinned unintentionally and that sin does not involve a planned rebellion against God's will, so that "sin that does not bring death" this is the kind of sin that does not result in eternal death or does not lead to eternal punishment, a sin that does not make a person certain to go to hell. Because for this sin has been provided forgiveness by God in the atonement of Christ.